Relationship between epicardial adipose tissue volume and coronary artery spasm. (1st February 2021) - Kataoka, Takashi; Harada, Ken; Tanaka, Akihito; Onishi, Tomohiro; Matsunaga, Shun; Funakubo, Hiroshi; Harada, Kazuhiro; Nagao, Tomoyuki; Shinoda, Norihiro; Marui, Nobuyuki; Niwa, Kiyoshi; Tashiro, Hiroshi; et al.
Abstract: Background: Epicardial adipose tissue (EAT) is considered to play a critical role in vascular endothelial function. Coronary artery spasm has been postulated to be a causal factor in vascular endothelial abnormalities and atherosclerosis. This study aimed to investigate the relationship between coronary artery spasm and EAT volume, total abdominal adipose tissue (AAT) area, and abdominal visceral adipose tissue (AVAT) area. Method: Among patients undergoing coronary computed tomography (CT) to evaluate coronary artery disease, we identified 110 patients who did not have significant coronary artery stenosis and underwent a coronary spasm provocation test with cardiac catheterization. They were divided into two groups according to the results of the spasm provocation test: spasm-positive and spasm-negative. EAT volume, total AAT area, and AVAT area were evaluated using CT images. Results: Seventy-seven patients were included in the spasm-positive group and 33 patients in the spasm-negative group. There were no significant differences in baseline clinical characteristics between the two groups, except for the prevalence of current smoking (48% vs. 27%, p = 0.04). EAT volume was significantly higher in the spasm-positive group (108 ± 38 mL vs. 87 ± 34 mL, p = 0.007), while no significant difference was seen in total AAT area (280 ± 113 cm 2 vs. 254 ± 128 cm 2, p = 0.32) or AVAT area (112 ± 54 cm 2 vs. 98 ± 55 cm 2, p = 0.27). Multivariate logistic analysis indicated that EAT volume (per 10 cm 3 ) (odds ratio, 1.198; 95% confidence interval, 1.035–1.388; p = 0.016) was a significant predictor of coronary artery spasm. Conclusion: Our results suggest that EAT has a strong association with coronary artery spasm, while AAT may not. Highlights: We assessed the relationship between coronary artery spasm and adipose tissues. Epicardial adipose tissue volume was higher in patients with coronary artery spasm. No relationship was observed between abdominal adipose tissues and coronary spasm. Increased epicardial adipose tissue volume was a predictor of coronary artery spasm.